The Concept of Excellence in Nike Advertisement “Unlimited You” - Yusuf Widjaja (Institute of Research and Community Outreach - Petra Christian University, 2017)
This thesis mainly deals with Barthes’s process of signification, denotation, connotation, and Lakoff’s and Johnson’s theory of metaphor in order to reveal the excellence concept in the branding of Nike video commercial “Unlimited You”. The focus of the writer’s analysis is the verbal and visual expressions in the video commercials. Those theories being used will help the writer in analysing the excellence concept and the use of verbal and visual expressions in the advertisement, then, figuring out the excellence concept used in the video commercials. The writer analyses one video commercial of Nike under the concept of “Unlimited Series” which is “Unlimited You”. This research uses qualitative content analysis by Krippendorff (2004) and Schreier (2012) to describe the concept of excellence in a systematic way. From the analysis, the writer found out that Nike aims to motivate and inspire its audience through the excellence concept. Furthermore, Nike defines the excellence concept as a form of success which comes in the form of ability to pass through the challenge. Nike associates success with high endurance, confidence, and optimism as pictured in the video commercials. The verbal and visual expressions are aimed to inspire and motivate the audiences to be optimistic, have confidence, and have high endurance to achieve success